Tensions in stakeholder perspectives on blockchain technology in sustainable food system transformation - Kingfisher, Levi; Nguyen Thi, Thuy Tien; Lehtonen, Sanni; Saidi, Trust; van de Burgwal, Linda; Loeber, Anne (Frontiers in Blockchain, 2025)
IntroductionBlockchain technology (BCT) has been proposed as a solution for many challenges facing global food systems, including environmental issues related to carbon, biodiversity, and other ecosystem services. Efforts to evaluate the potential of BCT to contribute to these issues are nascent and, in particular, little research has been conducted with the diversity of food system actors who will be implicated in and affected by the use of BCT.MethodsThis paper draws on a series of eleven co-creative workshops conducted with a wide range of food system actors, and highlights narratives about core issues regarding BCT’s impact on and relation to various challenges facing the food system, including environmental crises such as climate change and biodiversity loss. The workshops were conducted in 2023 and 2024, and involved over 100 participants including farmers, researchers, blockchain developers, policymakers, agribusiness companies, and other actors. These workshops began by developing idealized visions of blockchain-based future food systems, interrogated the barriers between the present and these futures, and co-created strategies to overcome these barriers.ResultsThe data that emerged from these workshops, including audio recordings as well as digital whiteboards, were subject to thematic analysis. We present three scenarios of BCT-enabled future food systems, which were produced from this analysis. Subsequently, we highlight four tensions–related to decentralization, inclusion, transparency, and tokenization–underlying these scenarios.DiscussionHow the core tensions we identified can be linked to the broader trend of datafication is discussed. We emphasis that how these tensions are negotiated between different, disparate actors will have significant implications on the impacts that BCT may have on food system transformation.